SUCCESSION OF BACTERIAL GENERA DURING ICED STORAGE OF THREE SPECIES OF TROPICAL PRAWNS, PENAEUS INDICUS,META PENAEUS, M. AFFINIS - SURENDRAN, P K; IYER, K MAHADEVA; GOPAKUMAR, K (Fishery Technology, 2017)
The native bacterial flora of ocean fresh tropical prawns, Penaeus indicus, Metapenaeus dobsoni and M. affinis was more or less similar, mainly consisting of Pseudomonas, Acinetobacter, Moraxella and Arthrobacter. A definite succession of bacterial genera during iced storage was observed in these prawns. As the day of ice storage increased, the proportion of Acinetobacter and Moraxella also increased considerably and consituted 70-78% of the flora at the t1me of spoilage. Spodage by Pseudomonas was very msignificant in prawns under iced storage.